2016
DOI: 10.20883/jms.2016.178
|View full text |Cite
|
Sign up to set email alerts
|

A study of ofloxacin and levofloxacin photostability in aqueous solutions

Abstract: Introduction. The photostability is one of the most important properties of drugs. A comprehensive study of ofloxacin (OFX) and levofloxacin (LVX) photostability in aqueous solutions was performed. Ofloxacin is a chemotherapeutic agent belonging to the second generation fluoroquinolones and is a racemate of (R)-(+)-ofloxacin and (S)-(-)-ofloxacin (LVX).Material and Methods. Samples of OFX and LVX were subjected to stress conditions of UV irradiation using a mercury-vapor lamp. The study involved development of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…LEV, which initially degrades rapidly, is thought to be the part in contact with air and moisture in the top layer of the FPSE. It is already known that LEV cannot remain stable in high temperatures, and excessive moisture can lead to hydrolysis and degradation. Besides temperature and moisture, oxidation is one of the major degradation factors for LEV. A forced degradation study for LEV reported by Dabhi et al clearly showed that at least 70% of LEV remained stable after 1 h under extreme pH values where acid or base hydrolysis occurred.…”
Section: Resultsmentioning
confidence: 99%
“…LEV, which initially degrades rapidly, is thought to be the part in contact with air and moisture in the top layer of the FPSE. It is already known that LEV cannot remain stable in high temperatures, and excessive moisture can lead to hydrolysis and degradation. Besides temperature and moisture, oxidation is one of the major degradation factors for LEV. A forced degradation study for LEV reported by Dabhi et al clearly showed that at least 70% of LEV remained stable after 1 h under extreme pH values where acid or base hydrolysis occurred.…”
Section: Resultsmentioning
confidence: 99%
“…For example, levofloxacin was widely reported to degrade by UV radiation in both aqueous [103,104] and bulk solid form [105,106], as well as in a mixture with paracetamol [107]. The photolysis produced some toxic and allergenic products.…”
Section: Fluoroquinolones Multi-component Developmentmentioning
confidence: 99%
“…Besides the low solubility, instability towards light also becomes the main problem of fluoroquinolones [2,4,5]. Photolysis produces toxic substances immediately after UV exposure, in both liquid [103,104] and solid forms [105][106][107].…”
Section: Fluoroquinolone-nsaid Multi-componentsmentioning
confidence: 99%
“…Wastewater treatment via photocatalysis for the efficient removal of CIP and LEV was a subject of concern in many articles, whereas the review articles presented by Shurbaji et al [1] and Saya et al [24] represent a good deal to these researches. However, analytical methods proposed for simultaneous estimation of either drug with its photodegradation products are limited, and usually employ high-performance liquid chromatography coupled with mass spectrometry (HPLC/MS) [25][26][27][28]. Even though it has remarkable advantages, many limitations hinder the use of HPLC/MS widely: it requires experienced trained analysts for its operation, has a high cost in terms of analysis and maintenance, only employs volatile buffers and consumes large volumes of organic solvents contradicting basic principles of green chemistry [29].…”
Section: Introductionmentioning
confidence: 99%